Photonic Crystal Fiber Sensor Design for Enhanced Tumor Detection: Structural Optimization and Sensitivity Analysis - Sharma, Sunil; Tharani, Lokesh (Photonics Letters of Poland, 2024)
This paper introduces an advanced Photonic Crystal Fiber (PCF) sensor tailored for the sensitive detection of tumor cells in cerebrospinal fluid (CSF), particularly relevant for leptomeningeal spread diagnosis. The PCF sensor leverages guided mode resonance (GMR) for its unique optical properties, with the resonant wavelength being highly sensitive to refractive index variations. A comprehensive sensitivity analysis is conducted, considering key structural parameters such as pitch and diameter, material properties including the refractive index of the core and liquid filling, and environmental factors like temperature and pressure. Proposed approach integrates a specific biomarker, the refractive index variation induced by the presence of tumor cells (Δn), into the PCF sensor design. The calibration curve, developed through experimental data, correlates observed changes in resonance wavelength (Δλres) with varying concentrations of tumor cells in the CSF. The PCF's dynamic response is optimized for rapid and precise detection, while uniform sensitivity across the sensing depth and volume is ensured. These findings demonstrate the potential of the proposed PCF sensor for accurate and early-stage tumor detection, contributing to the advancement of photonic sensing technologies in medical diagnostics. Full Text: PDF References E. Yablonovitch, "Inhibited Spontaneous Emission in Solid-State Physics and Electronics", Phys. Rev. Lett. 58, 2059 (1987). CrossRef M.F.H. Arif, K. Ahmed, S. Asaduzzaman, M.A.K. Azad, "Design and optimization of photonic crystal fiber for liquid sensing applications, Photonic Sens. 6(3), 279 (2016). CrossRef Y. Kamiura, T. Kurisawa, C. Fujikawa, and O. Mikami, "Polymer Spot Size Expanders for High Efficiency Optical Coupling in Optical Interconnection", Photonics Lett. Pol., 14(3), 62 (2022). CrossRef S. Sharma, L. Tharani, R.K. Sharma, S. Sharma, L. Tharani, R.K. Sharma, Proceedings of ICAIAA 2019 Springer, Singapore (2020). CrossRef